Painting the cannon's roar : music, the visual arts, and the rise of an attentive public in the age of Haydn, c.1750 to c1810 /: music, the visual arts, and the rise of an attentive public in the age of Haydn, c.1750 to c1810. (2017) - Unknown
No abstract available